Effects of Ca/P molar ratios on regulating biological functions of hybridized carbon nanofibers containing bioactive glass nanoparticles. (7th April 2017) - Cheng, Dan; Liu, Deping; Tang, Tianhong; Zhang, Xiurui; Jia, Xiaolong; Cai, Qing; Yang, Xiaoping
Abstract: Biological functions of hybridized carbon nanofibers (CNFs) depend closely on the incorporated bioactive components. For hybridized CNFs containing bioactive glass (BG) nanoparticles (CNF/BG), chemical compositions of BG nanoparticles might have decisive effects on their cell affinity and osteocompatibility. Herein, three hybridized CNF/BGs were produced by incorporating 68S-type BG nanoparticles with different Ca/P molar ratios (1.0, 1.67 or 2.5) into CNFs via a sol–gel/electrospinning and carbonization method. Structural evolution of these hybridized CNF/BGs was studied in relation to their Ca/P molar ratios. Crystalline wollastonite was found to be the dominant phase at a high feeding Ca/P molar ratio (i.e. 2.5), but weak crystallized hydroxyapatite was the main phase at the low feeding Ca/P molar ratio (i.e. 1.0). These findings were correlated to the biological functions of the resulted CNF/BG hybrids including apatite formation ability in simulated body fluid and osteoblast behaviors in in vitro culture. All the CNF/BG hybrids displayed a strong affinity for inducing apatite deposition, showing insignificant difference after the initial nucleation stage, while they behaved differently in promoting the proliferation and osteogenic differentiation of osteoblasts. The fastest proliferation rate and the highest expression of alkaline phosphatase activity was found on the CNF/BG (Ca/P = 1.0). The results suggested a feasible way to upregulate osteoblast behaviors is by changing the feeding Ca/P molar ratios in the preparation of CNF/BG hybrids for potential bone repairing applications.